"They never told us that Black is beautiful": Fostering Black joy and Pro-Blackness pedagogies in early childhood classrooms. (September 2022) - Williams, Michelle Grace
Black Art in various forms has long been used by people in the African Diaspora to promote Black joy and Pro-Blackness yet it is often not included in language and literacy early childhood pedagogies to uplift Black children in North American schools. Likewise, many anti-racist early childhood research studies focus on the challenges faced by Black people with little emphasis on Black joy and Pro-Black narratives and the ways they are central to our psychic preservation and survival in the fight against anti-Black racism (Dunn D and Love B, 2020; Ladson-Billings, 2019b). As a child, Nina Simone's Young Gifted and Black song lyrics rang true as the source of my Black joy was knowing the brilliance of Black people and being proud of our resistance to anti-Black racism. Growing up in the Jamaican context I heard the reggae version of her song rendered by Reggae artistes Marcia Griffiths and Bob Marley also Pro-Black advocates who contributed to my racial pride. Contemporary Jamaican Reggae artists like Chronixx with his song Black is Beautiful continue to promote these racial affirming messages. In this article, I focus on ways teachers can learn to promote Black Joy and Pro-Blackness in the early years as I introduce the notion of an African Diaspora Racial Literacy pedagogy that celebrates and fosters racial pride using Black music and poetry. By coining African Diaspora Racial Literacy, I refer to an instructional approach that draws from positive affirming racial messages from the African Diaspora to promote Black joy and racial pride, raise children's critical consciousness, and prepare children to be able to take action against anti-Black racism. Through the lenses of Pro-Black Jamaican Intellectual Thought, critical race, Black Feminist, and decolonizing perspectives, I explore Jamaican Black Art literacies (e.g. song and poetry) and provide recommendations for teachers of children of African descent that center Black joy and Pro-Blackness as resistance to anti-Black racism in early childhood pedagogy and practice.